Corrosion-resistant lead-acid battery pole plate as well as preparation method and application thereof
By coating the mixture of graphene oxide @2-mercapto-5-benzimidazole sodium sulfonate dihydrate @Ag NCs composite solution and poly3,4-ethylenedioxythiophene-polystyrene sulfonic acid solution on the gate surface of the lead-acid battery panel, the poor conductivity and dispersion problems caused by graphene oxide agglomeration are solved, and the corrosion resistance and performance of the battery are improved.
Patent Information
- Application Number
- CN202510132977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, direct mixing of poly3,4-ethylenedioxythiophene-polystyrene sulfonic acid and graphene oxide leads to agglomeration of graphene oxide, poor conductivity and dispersion, and cannot effectively improve the performance and life of lead-acid batteries.
Graphene oxide @2-mercapto-5-benzimidazole sodium sulfonate dihydrate @Ag NCs composite solution and poly3,4-ethylenedioxythiophene-polystyrene sulfonic acid solution were used to form a conductive coating. Through the formation and uniform dispersion of nanosilver particles, the corrosion resistance and conductivity of the grid were improved.
Effectively form a dense protective layer, reduce grid corrosion, improve battery charging and discharging efficiency, extend battery recycling life, and simplify the preparation process, which is suitable for large-scale production.
Smart Images

Figure BDA0005262229490000101 
Figure BDA0005262229490000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a corrosion-resistant lead-acid battery plate and a preparation method and application thereof. Background Art
[0002] Modern society consumes more and more fossil fuels, and the environment is seriously polluted. New clean energy such as solar energy, tidal energy, wind energy, geothermal energy, etc. are attracting more and more attention, but such energy needs to be stored in batteries to be better used. Lead-acid batteries have the advantages of high energy density, long service life, low self-discharge rate, high charge and discharge efficiency, low cost, good environmental adaptability, and safety and reliability. These advantages make lead-acid batteries an important energy storage solution widely used in various fields. But at the same time, lead-acid batteries also have the problem of low cycle life, and are easily terminated due to grid corrosion.
[0003] Poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid) material has corrosion resistance and can protect the grid from corrosion, thereby extending the service life of the battery. However, its conductivity is poor, and coating it on the surface of the lead-acid battery grid is not conducive to improving the performance of the battery. It is necessary to improve its conductivity by doping with conductive materials such as graphene oxide. The patent with announcement number CN105990583B solves the problem of the end of the battery life of lead-acid batteries caused by grid corrosion by mixing poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid) and graphene oxide and coating them on the surface of the lead-acid battery grid. However, direct mixing cannot avoid the agglomeration of graphene oxide itself, resulting in the final improvement effect being not obvious. Summary of the invention
[0004] The purpose of the present invention is to provide a corrosion-resistant lead-acid battery plate and a preparation method and application thereof, so as to solve the problem that direct mixing cannot avoid the agglomeration of graphene oxide itself, resulting in the final improvement effect being not obvious.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] In a first aspect, a corrosion-resistant lead-acid battery plate is provided, wherein the surface of the lead-acid battery grid is coated with a conductive coating, wherein the conductive coating is obtained by mixing a poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
[0007] Furthermore, the thickness of the conductive coating is 0.1-0.3 mm.
[0008] In a second aspect, a method for preparing a corrosion-resistant lead-acid battery plate comprises the following steps:
[0009] 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution were mixed, stirred for 2-3 hours, and then the lead-acid battery grid was immersed in it for 2-3 minutes, taken out and dried to obtain a corrosion-resistant lead-acid battery plate.
[0010] Among them, the volume ratio of 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution is 1:0.1-0.2.
[0011] Furthermore, the drying temperature is 70-80° C. and the drying time is 1-2 h.
[0012] Furthermore, the preparation method of the graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution is as follows:
[0013] Step A1: 0.08 mol / L aqueous solution of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate and 0.01 mol / L aqueous solution of silver nitrate were mixed, and then 0.5 mol / L aqueous solution of sodium borohydride was added, and the mixture was stirred at room temperature for 8-9 hours to obtain a sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution;
[0014] Wherein, the volume ratio of the sodium 2-mercapto-5-benzimidazole sulfonate dihydrate aqueous solution, the silver nitrate aqueous solution and the sodium borohydride aqueous solution is 1:1:0.2-0.25.
[0015] Silver nitrate ionizes into silver ions in water, and sodium borohydride, as a strong reducing agent, can reduce silver ions to silver atoms, thereby forming nanosilver particles. The thiol group in sodium 2-mercapto-5-benzimidazole sulfonate dihydrate has a strong interaction with silver, and the electron-rich atoms on its heterocyclic ring can also coordinate with silver. The sulfonic acid group contained in it can give the prepared silver nanoclusters good water solubility, thereby stabilizing the nanosilver particles and preventing them from agglomerating, forming a uniform sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution.
[0016] Step A2: The sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution was mixed with a 0.5 g / L graphene oxide aqueous solution and stirred for 1-2 h to obtain a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
[0017] Among them, the volume ratio of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution to graphene oxide aqueous solution is 7-8:1.
[0018] Sodium 2-mercapto-5-benzimidazole sulfonate dihydrate in the sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution contains sulfonic acid groups, which are negatively charged and can interact with the positive charges on the surface of graphene oxide, thereby reducing the electrostatic repulsion between particles, avoiding agglomeration, improving the dispersibility of graphene oxide, and enabling graphene oxide to fully play a conductive role.
[0019] A third aspect is the use of a corrosion-resistant lead-acid battery plate in the preparation of a lead-acid battery.
[0020] Beneficial effects of the present invention:
[0021] 1. The present invention prepares a corrosion-resistant lead-acid battery plate, wherein the surface of the lead-acid battery grid is coated with a conductive coating, which is obtained by mixing a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid) solution with a graphene oxide@2-mercapto-5-benzimidazole sulfonate sodium dihydrate@Ag NCs composite solution. The size of the nanosilver particles is very small, which gives them an extremely high specific surface area and surface energy. This small size effect enables the nanosilver particles to adhere more closely to the grid surface, forming a dense protective layer, effectively isolating the direct contact between the electrolyte and the grid, thereby reducing corrosion. Nanosilver is conductive, which can reduce the energy loss of the battery during the charging and discharging process, improve the charging and discharging efficiency of the battery, and help extend the cycle life of the battery. Sodium 2-mercapto-5-benzimidazole sulfonate dihydrate contains mercapto, benzothiazole and sulfonic acid groups, among which the electron-rich atoms on the mercapto and heterocyclic rings can coordinate with silver ions, thereby improving the dispersibility of nanosilver, making the nanosilver evenly distributed on the surface of the lead-acid battery grid, further improving the corrosion resistance of the grid, improving the performance of the battery and extending the service life of the battery. Sulfonic acid groups can improve the dispersibility of graphene oxide, thereby solving the problem of poor dispersibility of graphene oxide. Graphene oxide has excellent electrical conductivity and mechanical properties. The uniform dispersion of this substance can further improve the corrosion resistance of the grid, improve the performance of the battery and extend the service life of the battery.
[0022] 2. The preparation method of the present invention is simple, highly controllable, and is conducive to large-scale production.
[0023] 3. The present invention prepares a lead-acid battery plate with excellent cycle performance and corrosion resistance by precisely controlling the addition amount of graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution. When the addition amount is too much, the excess graphene oxide sheets are prone to stacking and agglomeration, affecting its conductivity and dispersibility, thereby reducing performance. When the addition amount is too low, an effective protective layer cannot be formed on the grid surface, thereby failing to effectively prevent corrosion. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Preparation Example 1
[0026] The preparation method of the graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution in this preparation example is:
[0027] Step A1: 5 mL of 0.08 mol / L 2-mercapto-5-benzimidazole sulfonate sodium dihydrate aqueous solution (2-mercapto-5-benzimidazole sulfonate sodium dihydrate) and 5 mL of 0.01 mol / L silver nitrate aqueous solution were mixed, and then 1 mL of 0.5 mol / L sodium borohydride aqueous solution was added, and the mixture was stirred at room temperature for 8 h to obtain 2-mercapto-5-benzimidazole sulfonate sodium dihydrate@Ag NCs solution;
[0028] Step A2: 7 mL of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution was mixed with 1 mL of 0.5 g / L graphene oxide aqueous solution and stirred for 1 h to obtain a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
[0029] Preparation Example 2
[0030] The preparation method of the graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution in this preparation example is:
[0031] Step A1: 5 mL of 0.08 mol / L 2-mercapto-5-benzimidazole sulfonate sodium dihydrate aqueous solution (2-mercapto-5-benzimidazole sulfonate sodium dihydrate) and 5 mL of 0.01 mol / L silver nitrate aqueous solution were mixed, and then 1 mL of 0.5 mol / L sodium borohydride aqueous solution was added, and the reaction was stirred at room temperature for 9 h to obtain 2-mercapto-5-benzimidazole sulfonate sodium dihydrate@Ag NCs solution;
[0032] Step A2: 7.5 mL of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution was mixed with 1 mL of 0.5 g / L graphene oxide aqueous solution and stirred for 2 h to obtain a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
[0033] Preparation Example 3
[0034] The preparation method of the graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution in this preparation example is:
[0035] Step A1: 5 mL of 0.08 mol / L 2-mercapto-5-benzimidazole sulfonate sodium dihydrate aqueous solution (2-mercapto-5-benzimidazole sulfonate sodium dihydrate) and 5 mL of 0.01 mol / L silver nitrate aqueous solution were mixed, and then 1 mL of 0.5 mol / L sodium borohydride aqueous solution was added, and the reaction was stirred at room temperature for 8.5 h to obtain 2-mercapto-5-benzimidazole sulfonate sodium dihydrate@Ag NCs solution;
[0036] Step A2: 8 mL of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution was mixed with 1 mL of 0.5 g / L graphene oxide aqueous solution and stirred for 1.5 h to obtain a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
[0037] Comparative Example 1
[0038] The preparation method of the graphene oxide@sodium dodecyl sulfate@Ag NCs composite solution in this comparative example is:
[0039] Step A1: 5 mL of 0.08 mol / L sodium dodecyl sulfate aqueous solution and 5 mL of 0.01 mol / L silver nitrate aqueous solution were mixed, and then 1 mL of 0.5 mol / L sodium borohydride aqueous solution was added, and the mixture was stirred at room temperature for 8 h to obtain a sodium dodecyl sulfate@Ag NCs solution;
[0040] Step A2: 7 mL of sodium dodecyl sulfate@Ag NCs solution was mixed with 1 mL of 0.5 g / L graphene oxide aqueous solution and stirred for 1 h to obtain a graphene oxide@sodium dodecyl sulfate@Ag NCs composite solution.
[0041] Example 1
[0042] The present embodiment provides a corrosion-resistant lead-acid battery plate, wherein the surface of the lead-acid battery grid is coated with a conductive coating, wherein the conductive coating is obtained by mixing a 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution, and the thickness of the conductive coating is 0.1 mm.
[0043] The method for preparing a corrosion-resistant lead-acid battery plate comprises the following steps:
[0044] 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution prepared in Preparation Example 1 were mixed, stirred for 2 hours, and the lead-acid battery grid was immersed for 2 minutes, taken out and dried at a temperature of 70°C for 1 hour to obtain a corrosion-resistant lead-acid battery plate. The volume ratio of the poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and the graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution was 1:0.1.
[0045] Example 2
[0046] The present embodiment provides a corrosion-resistant lead-acid battery plate, wherein the surface of the lead-acid battery grid is coated with a conductive coating, wherein the conductive coating is obtained by mixing a 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution, and the thickness of the conductive coating is 0.3 mm.
[0047] The method for preparing a corrosion-resistant lead-acid battery plate comprises the following steps:
[0048] 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution prepared in Preparation Example 2 were mixed, stirred for 3 hours, and the lead-acid battery grid was immersed for 3 minutes, taken out and dried at a temperature of 70°C for 1 hour to obtain a corrosion-resistant lead-acid battery plate. The volume ratio of the poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and the graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution was 1:0.125.
[0049] Example 3
[0050] The present embodiment provides a corrosion-resistant lead-acid battery plate, wherein the surface of the lead-acid battery grid is coated with a conductive coating, wherein the conductive coating is obtained by mixing a 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution, and the thickness of the conductive coating is 0.2 mm.
[0051] The method for preparing a corrosion-resistant lead-acid battery plate comprises the following steps:
[0052] 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution prepared in Preparation Example 3 were mixed, stirred for 3 hours, and the lead-acid battery grid was immersed for 3 minutes, taken out and dried at a temperature of 75°C for 1 hour to obtain a corrosion-resistant lead-acid battery plate. The volume ratio of the poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and the graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution was 1:0.15.
[0053] Example 4
[0054] The present embodiment provides a corrosion-resistant lead-acid battery plate, wherein the surface of the lead-acid battery grid is coated with a conductive coating, wherein the conductive coating is obtained by mixing a 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution, and the thickness of the conductive coating is 0.2 mm.
[0055] The method for preparing a corrosion-resistant lead-acid battery plate comprises the following steps:
[0056] 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution prepared in Preparation Example 3 were mixed, stirred for 3 hours, and the lead-acid battery grid was immersed for 3 minutes, taken out and dried at a temperature of 75°C for 1.5 hours to obtain a corrosion-resistant lead-acid battery plate. The volume ratio of the poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution to the graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution was 1:0.175.
[0057] Example 5
[0058] The present embodiment provides a corrosion-resistant lead-acid battery plate, wherein the surface of the lead-acid battery grid is coated with a conductive coating, wherein the conductive coating is obtained by mixing a 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution, and the thickness of the conductive coating is 0.2 mm.
[0059] The method for preparing a corrosion-resistant lead-acid battery plate comprises the following steps:
[0060] 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution prepared in Preparation Example 3 were mixed, stirred for 3 hours, and the lead-acid battery grid was immersed for 3 minutes, taken out and dried at a temperature of 80°C for 2 hours to obtain a corrosion-resistant lead-acid battery plate. The volume ratio of the poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and the graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution was 1:0.2.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 1 is that the graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution in Example 1 is replaced by the product prepared in Control Example 1, and the remaining raw materials and steps are the same as Example 1.
[0063] Comparative Example 2
[0064] Compared with Example 1, this comparative example 1 is different in that the "graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution" in Example 1 is replaced by "0.5 g / L graphene oxide aqueous solution", and the remaining raw materials and steps are the same as Example 1.
[0065] Comparative Example 3
[0066] Compared with Example 1, this comparative example 1 is different in that the volume ratio of the poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and the graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution in Example 1 is replaced with 1:0.05, and the other raw materials and steps are the same as Example 1.
[0067] Comparative Example 4
[0068] Compared with Example 5, this comparative example 1 is different in that the volume ratio of 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution in Example 5 is replaced with 1:0.25, and the other raw materials and steps are the same as Example 5.
[0069] The corrosion-resistant lead-acid battery plates prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were used as positive electrodes, and the negative grid of the commonly used lead-calcium-tin-aluminum alloy was used as the negative electrode. The negative electrode lead paste was prepared by mixing 100 parts of lead powder, 2 parts of barium sulfate, 0.2 parts of sodium lignin sulfonate, 0.2 parts of carbon black, 10 parts of deionized water, and 10 parts of 14 mol / L dilute sulfuric acid. The negative electrode was filled with an AGM diaphragm to separate the positive and negative electrodes, and assembled into a prototype battery. 1.300 g·cm -3 The H2SO4 solution is used to obtain the battery to be tested. The performance test of the battery to be tested is carried out, and the test items are as follows:
[0070] 1. Corrosion resistance test: The prototype battery was placed in a 60℃ water bath environment and connected in series for a constant current charging corrosion test. The μC-XCF08 charge and discharge tester was used for a constant current polarization test. The apparent corrosion current density of the corrosion grid was 2.3 mA cm -2 , the constant current corrosion time is 300h. After the grid corrosion is completed, the corrosion products on the grid surface are removed by soaking in sugar-alkali solution. The corroded grid is washed with deionized water and vacuum dried and then weighed (m2). The weight loss of the grid before and after electrochemical corrosion (m1-m2) is calculated, and then the average corrosion rate of the grid is calculated. The results are shown in Table 1.
[0071] 2. Battery life test: refer to GB19638.2-2005 "Fixed Valve-Controlled Sealed Lead-Acid Battery" standard, conduct accelerated floating charge cycle durability test on the battery, conduct the first 3-hour rate (C3) capacity test on the battery to be tested at 25°C, and fully charge the battery, charge at a constant voltage of 2.25V / cel for 30 days at 60°C, and then cool the battery at 25°C for 24 hours before conducting C3 capacity test at room temperature. Each test cycle is equivalent to a floating charge service life of 1 year, until the room temperature C3 capacity is lower than 80% of the rated C3 capacity, and the battery discharge capacity is lower than 80% of the rated capacity, it is judged as failure, and the test is terminated. The effective cycle number of the battery accelerated floating charge test is shown in Table 2 below.
[0072] Table 1
[0073] project <![CDATA[Average corrosion rate (mg / h.cm 2 )]]> Example 1 0.27 Example 2 0.23 Example 3 0.21 Example 4 0.18 Example 5 0.14 Comparative Example 1 0.43 Comparative Example 2 0.62 Comparative Example 3 0.34 Comparative Example 4 0.26
[0074] As can be seen from Table 1, the corrosion resistance of the plates prepared by Examples 1 to 5 of the present invention is significantly better than that of the plates prepared by Comparative Examples 1 to 4. Comparative Example 1 does not contain thiol groups and electron-rich atoms on heterocyclic rings, and cannot coordinate with silver ions, so the dispersibility of nanosilver is poor and the corrosion resistance is reduced; in Comparative Example 2, graphene oxide is directly added, the dispersibility of graphene oxide is poor, and the corrosion resistance is reduced; in Comparative Examples 3 and 4, the addition amount of graphene oxide @ sodium 2-mercapto-5-benzimidazole sulfonate dihydrate @ Ag NCs composite solution is lower than that of Example 1 and higher than that of Example 5, respectively. From the test results, it can be seen that the corrosion resistance of both is lower than that of Example 1 and Example 5, indicating that the addition amount of the present invention is the optimal amount, and too low or too much addition of the composite solution is not conducive to the improvement of the comprehensive performance of the plate.
[0075] Table 2
[0076]
[0077]
[0078] It can be seen from Table 2 that the service life of the batteries prepared in Examples 1 to 5 of the present invention is significantly better than the service life of the batteries prepared in Comparative Examples 1 to 4.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A corrosion-resistant lead-acid battery plate, characterized in that: The surface of the lead-acid battery grid is coated with a conductive coating, which is obtained by mixing a poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution with a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
2. A corrosion-resistant lead-acid battery plate according to claim 1, characterized in that: The thickness of the conductive coating is 0.1-0.3 mm.
3. A method for preparing a corrosion-resistant lead-acid battery plate according to any one of claims 1-2, characterized in that: The following steps are involved: 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution were mixed, stirred for 2-3 hours, and then the lead-acid battery grid was immersed in it for 2-3 minutes, taken out and dried to obtain a corrosion-resistant lead-acid battery plate.
4. The method for preparing a corrosion-resistant lead-acid battery plate according to claim 3, characterized in that: The volume ratio of 1 g / L poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid solution and graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution is 1:0.1-0.
2.
5. The method for preparing a corrosion-resistant lead-acid battery plate according to claim 3, characterized in that: The drying temperature is 70-80℃.
6. The method for preparing a corrosion-resistant lead-acid battery plate according to claim 3, characterized in that: The drying time is 1-2h.
7. The method for preparing a corrosion-resistant lead-acid battery plate according to claim 3, characterized in that: The preparation method of the graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution is as follows: Step A1: 0.08 mol / L aqueous solution of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate and 0.01 mol / L aqueous solution of silver nitrate were mixed, and then 0.5 mol / L aqueous solution of sodium borohydride was added, and the mixture was stirred at room temperature for 8-9 hours to obtain a sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution; Step A2: The sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution was mixed with a 0.5 g / L graphene oxide aqueous solution and stirred for 1-2 h to obtain a graphene oxide@sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs composite solution.
8. The method for preparing a corrosion-resistant lead-acid battery plate according to claim 7, characterized in that: In step A1, the volume ratio of the aqueous solution of sodium 2-mercapto-5-benzimidazole sulfonate dihydrate, the aqueous solution of silver nitrate and the aqueous solution of sodium borohydride is 1:1:0.2-0.
25.
9. The method for preparing a corrosion-resistant lead-acid battery plate according to claim 7, characterized in that: In step A2, the volume ratio of the sodium 2-mercapto-5-benzimidazole sulfonate dihydrate@Ag NCs solution to the graphene oxide aqueous solution is 7-8:
1.
10. Use of a corrosion-resistant lead-acid battery plate according to any one of claims 1 to 2 in the preparation of lead-acid batteries.
Citation Information
Patent Citations
A high-performance corrosion-resistant composite coated grid for lead-acid batteries and its preparation method
CN105990583B
Cited By
An anti-corrosion and anti-expansion positive plate grid of lead-acid battery and a preparation method thereof
CN122762696A